2012
DOI: 10.1111/j.1365-2966.2012.21555.x
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the intracluster light at z∼1

Abstract: A significant fraction of the total photospheric light in nearby galaxy clusters is thought to be contained within the diffuse intracluster light (ICL), which extends hundreds of kpc from cluster cores. The study of the ICL can reveal details of the evolutionary histories and processes occurring within galaxy clusters; however, since it has a very low surface brightness, it is often difficult to detect. We present here the first measurements of the ICL as a fraction of the total cluster light at z ∼ 1 using de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
100
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(111 citation statements)
references
References 41 publications
11
100
0
Order By: Relevance
“…Diffuse light becomes an important aspect in clusters of galaxies as shown by recent studies (Gregg & West 1998;Mihos et al 2005;Zibetti et al 2005;González et al 2007;Krick & Bernstein 2007;Rudick et al 2010;Burke et al 2012). It finds its origin at least partly in matter ejections from galaxies during galaxy-galaxy or galaxy-cluster potential interactions (see e.g.…”
Section: ) Is In Good Agreementmentioning
confidence: 92%
See 1 more Smart Citation
“…Diffuse light becomes an important aspect in clusters of galaxies as shown by recent studies (Gregg & West 1998;Mihos et al 2005;Zibetti et al 2005;González et al 2007;Krick & Bernstein 2007;Rudick et al 2010;Burke et al 2012). It finds its origin at least partly in matter ejections from galaxies during galaxy-galaxy or galaxy-cluster potential interactions (see e.g.…”
Section: ) Is In Good Agreementmentioning
confidence: 92%
“…Guennou et al (2012) used deep HST ACS data to detect diffuse light for ten clusters between z = 0.4 and 0.8 and did not detect any significant variation in the cluster diffuse light content with redshift. By applying a somewhat less sophisticated method, Burke et al (2012) extended this search to a sample of six clusters at z ∼ 1 based on VLT/HAWK-I data, and found that intracluster light (hereafter ICL) only composed (1−4)% of the total cluster light.…”
Section: ) Is In Good Agreementmentioning
confidence: 99%
“…Stars that have been removed from their parent galaxy can be observed in galaxy clusters as a diffuse light, called intracluster light. However, its observational detection is very difficult due to the extremely low surface brightness of the intra-cluster light, which contains ∼ 10%−30% of the total optical luminosity of the galaxy clusters (Gregg and West 1998;Mihos et al 2005;Krick and Bernstein 2007;Burke et al 2012;Mihos 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Assessing the true fraction of the ICL component relative to the individual galaxies is a continuing and difficult issue since it requires careful separation of the ICL profile from the giant galaxies in the cluster, but is almost certainly in the range 10-50% for rich clusters and even groups (Gonzalez et al 2005; Da Rocha & Mendes de Oliveira 2005; Seigar et al 2007;Rudick et al 2011;Giallongo et al 2014;Jiménez-Teja & Dupke 2016). The growth of the ICL is an ongoing process with much of it happening since redshift z ∼ 1 (Burke et al 2012(Burke et al , 2015Adami et al 2013;Presotto et al 2014), so the total luminosity in the ICL and its degree of substructure (clumps and tidal streams) are indicative of the dynamical evolutionary state of the cluster.…”
mentioning
confidence: 99%